Predictors of Learning Styles in Students of Kerman University of Medical Sciences Iran - Hajar Shafian; Hajar Shafian; Mansooreh Azizzadeh-Forouzi; Ali Akbar Haghdoost; Behshid Garrusi; Ali Akbar Haghdoost; Soodabeh Navadeh (Kerman University of Medical Sciences, 2014)
Background & Objective: Learning style is a distinct behavior for gaining knowledge and skills through study or experience Personality is a series of relatively stable characteristics which distinguish a person from others The key to involving learners in the learning process is their preferences and learning styles and identifying factors affecting these variables In this regard the predictor variables of learning styles must be accurately identified so as to improve educational conditions This study aimed to determine factors predictive of learning styles of the students of Kerman University of Medical Sciences Iran In addition the impact of demographic factors on their characteristics will be discussed   Methods: This was a crosssectional study Data collection was performed by a questionnaire including demographic data personality test (NEO) the Learning style inventory and the Kolb Learning Style Questionnaire For data analysis central tendency and dispersion measures chisquare Spearman correlation coefficient and logistic regression tests were used   Results: The results show that most of the participants in this study were single women Mean age of participants was 2141 ± 296 years Most students (4431%) used assimilating learning style Based on the results of these personality types nearly a third of students (282%) were of the conscientious (responsible) character type The results showed that only gender is a predictor of learning styles   Conclusion: More attention to students learning styles results in the perfect use of teaching practices and increasing and enhancement of students capabilities Moreover by identifying students preferred learning styles and changing teaching methods the students enthusiasm for learning can be increased